THE FORMATION FACTORS OF ENGLISH LANGUAGE APHORISMS. APHORISTIC TEXTS - Eshmuratov Umidjon Temurovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstaract: As aphorisms have been for millennia anthologized and de- anthologized, revived and mutilated, quoted and misquoted, they constitute their own cultural network. As such, a philological understanding of aphorisms is as necessary as a philosophical one: that is to say, one must examine not only their internal meaning but also the circumstances of their material production, transmission, and reception in history.